2014
DOI: 10.1007/s10680-014-9329-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gender Norms Between Countries: Are They Valid? The Issue of Measurement Invariance

Abstract: The values and attitudes towards gender roles are often investigated and compared from a cross-country perspective without the proper statistical treatment of the measurement invariance (MI) assessment. This implies that the conclusions based on composite scales of gender norms, gender role attitudes or gender egalitarianism, to name only a few, may be questionable. In this study, we address this lack by investigating the cross-country MI properties of the Gender Equality Scale (GES) based on World Value Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Desa and Carstens (2015) proposed to apply this approach in the future in large-scale assessment contexts such as the Programme for International Student Assessment (PISA) and the Teaching and Learning International Survey (TALIS), as it legitimates mean comparisons in dozens of groups without requiring full measurement invariance. Weziak-Bialowolska (2014) tested gender ideology in the World Value Survey with CFA with and without alignment. She reported different patterns of country factor means from these two methods, and suggested that comparisons of the country rankings were valid provided that a correction for noninvariance of certain factor loadings and/or intercepts is applied in the alignment framework.…”
Section: The State-of-the-art In Assessing Cross-cultural Comparabilitymentioning
confidence: 99%
“…Desa and Carstens (2015) proposed to apply this approach in the future in large-scale assessment contexts such as the Programme for International Student Assessment (PISA) and the Teaching and Learning International Survey (TALIS), as it legitimates mean comparisons in dozens of groups without requiring full measurement invariance. Weziak-Bialowolska (2014) tested gender ideology in the World Value Survey with CFA with and without alignment. She reported different patterns of country factor means from these two methods, and suggested that comparisons of the country rankings were valid provided that a correction for noninvariance of certain factor loadings and/or intercepts is applied in the alignment framework.…”
Section: The State-of-the-art In Assessing Cross-cultural Comparabilitymentioning
confidence: 99%
“…Internalised gender norms and relations of the country of origin may be challenged and modified in the country of reception via acculturation processes and socioeconomic integration [32]. However, we acknowledge that cultural differences may in some contexts be more accentuated within countries, as a body of literature highlights [36,37].…”
Section: Gender Migration and Healthmentioning
confidence: 99%
“…According to Davidov, Dülmer, Schlüter, Schmidt, and Meuleman (2012) measurement invariance, in particular scalar noninvariance, represents one of the most serious threats to cross-cultural research. The literature on adult samples shows that there are significant differences in countries’ norms on gender equality between western Europe and central and eastern Europe (Weziak-Bialowolska, 2015). Moreover, there are differences between central and eastern European countries as well, with Romania being one of the lowest-scoring countries regarding attitudes toward gender equality.…”
Section: The Present Studymentioning
confidence: 99%